Exogenous phytase for better utilization of parboiled rice polish based diet on the growth and meat yield of Japanese quail - Sarkar, DK; Mahiuddin, M; Ali, MS; Azad, MMH; Howlider, MAR (Bangladesh Journal of Animal Science, 2012)
For the abundant use of parboiled rice polish (PRP), dietary grains were replaced by 200g/kg and 400g/kg PRP with or without phytase supplementation. A total of 108 seven days old Japanese quails were fed ad libitum up to 35 days of age for better utilization of PRP. Increasing PRP with or without phytase supplementation did not influence live weight and feed intake. Supplementation of phytase improved feed conversion only in diet containing 200g/kg PRP (p<0.05). Feed cost/kg quail decreased with the addition of phytase at 200g/kg PRP diet, but increased on 400g/kg PRP diet. Dressing yield was improved (p<0.05) in 200g/kg PRP diet with phytase supplementation. There was an increase (p<0.05) in thigh meat for application of phytase in 400g/kg PRP diet. Heart weight increased (p<0.05) on 200g/kg PRP diet and decreased on 400g/kg PRP. It was concluded that substitution of costly grains by 200g/kg cheaper PRP with phytase might reduce the feed cost without affecting feed intake, live weight and meat yield of quails. DOI: http://dx.dol.org/10.3329/BJAS.v40i1-2.10681 Bang. J. Anim. Sci. 2011. 40 (1-2): 8-12